Peran Pemerintah Lokal Dalam Pembangunan Perkotaan di Negara Berkembang - Jhonny Patta (Journal of Regional and City Planning, 1996)
The relation between local government and urban development is dynamic and interactive. It is influenced by multinational relationship and global issues, but most of the impacts of multinational relationships and global issues are directly related to the role of national government and indirectly to the role of local government. Nevertheless, the role of local government in urban development cannot be simply explained by its position relative to the national government. Instead, it encompasses a complex set of behavior (Daland, ed.1969) and associated with other influences in formulating, deciding, and achieving general and specific goals of urban development. According to Sherwood (1969) ""¦ the examination of the role of local government involves more than the structure of reporting or authority relationships. The concept of role is more dynamic, in that it essentially calls for specification of the ways in which the unit will participate in a given system" (Daland, ed.1969).This the role of local government is open to other influences and interdependence to other roles in a given system. This stand points needs further explanations and answers in both the normative and the empirical sides. As a consequence, the role of local government must deal with the value, the process, and the goals of urban development. In this sense, this paper is concerned with the role of local government in urban development in the context of developing countries.The role of local government raises both descriptive and normative questions. What does the theory say? Flow can we explain (he urban-national relationship? What the local governments in developing countries do to their urban development? Flow does the local government and its bureaucracy behave? What factors determine the interdependencies between local government and other parties that are involved in urban development? What should the local governments do in a particular political setting? How can we draw the boundaries among roles? In the context of urban development in developing countries, how is power o be shared among roles? In current situation, how are such power distributions reflected in terms of urban activities and resources? What can be learned from those experiences? What are the impacts of what they do? What criteria should he learned in evaluating those impacts? What are the obstacles when they are playing their role? Based on the literature review, this paper tries to find a critical research question, concerning the role that local governments can play in the future. Are there any factors that can be used to bridge from what was done to describe what should be done in the future?